The effect of anion exchange on the electronic and optical properties of vacancy ordered double perovskites K2PdX6 (X = Cl, Br, I) using first principle calculations. Issue 17 (22nd November 2022) - Anbarasan, Radhakrishnan; Srinivasan, Manickam; Sundar, Jeyaperumal Kalyana; Morsi, Manal; Albalawi, Hind; Somaily, H. H.; Ramasamy, Perumalsamy
ABSTRACT: Recent studies are confirmed that lead-free perovskite is a possible alternative solution for conventional hybrid lead-based perovskites to achieve better photovoltaic efficiency. This work investigates the structural, mechanical, electronic, and optical properties of vacancy ordered double perovskite of K2 PdX6 (X = Cl, Br, I) for photovoltaic applications through the density functional theory at the HSE06 level of theory. The bond length of Pd-X is linearly increased while exchanging the anions from Cl to I. The mechanical study reveals that the vacancy-ordered double perovskites K2 PdCl6, K2 PdBr6, and K2 PdI6 are elastically classified as ductile materials. The K2 PdBr6 hold a favourable bandgap of 1.62 eV for single junctions solar cell applications. The studied perovskite bandgaps depend on the Pd-4d, s and p orbitals of anions. The optical study uncover that the studied perovskites are higher optical absorption in the visible regions. Based on calculated results, we conclude that these K2 PdBr6 vacancy ordered double perovskites might be suitable material for photovoltaic applications.